BIVARIATE NEW BETTER THAN USED CLASS OF LIFE DISTRIBUTIONS - RIZWAN*, U.; SATHIYARAJ, A. (International Journal of Mathematical Archive, 2018)
Some new results on Bivariate New Better than Used of order 3 (BNBU (3)) class of life distributions are obtained. Closure of the BNBU(3) class under convolution is given. Shock models where shocks are arriving according to homogeneous Poisson Process are established.